Peran dan Fungsi Kepolisian dalam Upaya Pencegahan Pelaku Geng Motor di Wilayah Surabaya (Studi Kasus Polrestabes Surabaya) - Briesa Salsabilla Alzahra; Sadjijono Sadjijono (Fakultas Hukum Universitas Bhayangkara Surabaya, 2026)
The recent rise in motorcycle gang activity has become a serious security threat. Motorcycle gang members tend to commit criminal acts such as assault, theft, robbery, and vandalism of public facilities, thereby creating a sense of insecurity among the public. This study analyzes the strategies and measures implemented by the Surabaya Metropolitan Police to combat motorcycle gang crime. The research method employed is a qualitative study using a case study approach. Data was collected through in-depth interviews with police officials, document analysis, and a review of the literature, including legislation and scientific journals. The results indicate that the Surabaya Metropolitan Police Department implements three integrated approaches in addressing motorcycle gangs: preventive, pre-emptive and repressive, The success of these efforts is also supported by strong collaboration between the police, local government, and active community participation. This study recommends reinforcing youth development programs, increasing community participation in maintaining neighborhood security, and the need for further research on the socioeconomic factors influencing the formation of motorcycle gangs.